A study on English translation of Chinese four-character idioms: Strategies and problems - Kang, Hongmei; Yang, Yang (Linguistics and Culture Review, 2022)
Chinese Four-character idioms are fixed phrases with four Chinese characters that have been used for a long time in Chinese. They are language units with richer meanings and equivalent grammatical functions than words. They are concise, easy to remember, and easy to use. Many idioms have two or more meanings. It is precisely for this reason that the English translation of Chinese idioms has brought considerable difficulties. In the process of translating idioms into English, it is difficult to be accurate, profound, and complete. Therefore, a variety of English translation techniques should be combined for translating Chinese four-character idioms. This paper analyzed the definition, characteristics, classification, and translatability of Chinese four-character idioms, and concluded three commonly applied strategies for translating Chinese four-character idioms into English: the literal translation, the free translation, and the combination of literal and free translation. Finally, some problems existing in the translation of Chinese four-character idioms are analyzed and summarized: poor acceptance by foreigners, loss of cultural elements, and unbalanced cultural status.